Photo-bio-degradability of agro waste and ethylene-propylene copolymers composites under abiotic and biotic environments - Kumar, A. Pratheep; Pandey, Jitendra K.; Kumar, Bijendra; Singh, R. P. (Journal of Polymers and the Environment, 2006)
Composites were prepared by two methods, (i) graft copolymerization (GFC) of isotactic polypropylene (PP) with maliec anhydride, (MAH) followed by esterification with coir fiber and (ii) by direct reactive mixing (DFC) of polypropylene (PP) and ethylene-propylene (EP) copolymers with MAH and peroxide with coir fiber. These composites, after molding in films (5 x 5 cm, - 100 mu m thickness) were examined for susceptibility to biological attack by measuring the percentage weight loss in compost upto 6 months, periodically, and fungal colonization on surface of the samples, when kept as sole carbon source for the growth of Aspergillus niger in culture medium upto 40 days. Photodegradation was evaluated by monitoring the variations in FT-IR spectrum and crack formation after successive treatment with UV light (>= 290 nm) for 0, 20, 50 and 100 h at 60 C in the presence of air. Specimens of virgin PP were taken as a reference during all period of photo and biodegradation studies. Significant changes were observed depending on the preparation methods during photodegradation and biodisintegration of composites. DFCs samples were disintegrated faster than GFCs during the composting whereas, in culture, GFCs were covered highly in well uniform way by fungi. It was observed that photo-oxidative ageing directly enhanced the biodegradability of composites as the increase in fungal growth rate and decrease in weight during composting were found. It was concluded that extent of compatibilization had a profound effect on photo-oxidation and biodisintegration of composite material; consequently ester bonds were main units during fungal consumption. Composition of monomers in copolymers was also showing significant effect on the degradability which decreased with increasing content of ethylene in ethylene-propylene (EP) copolymers.
Keywords: Biodegradation; biodisintegration and composting; composites; ethylene-propylene copolymers; photo-degradation

Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Tevtia, Amit K.; Singh, R. P. (Polymer Degradation and Stability, 2006)
The stabilization of polyolefins against gamma-sterilization has been studied with single or binary additive system. The present attempt is to utilize synergistic mixtures of stabilizers which are approved for food contact applications. Ethylene-propylene (EP) copolymer has been melt-mixed with hindered amine stabilizers (HAS), phenolic antioxidants and organo-phosphites (hydroperoxide decomposer). Samples were sterilized with different doses of gamma-radiation. Stabilization was characterized in terms of changes in the functional groups (oxidation products), tensile properties, yellowing and surface morphology by FTIR spectroscopy, Instron, colorimetry (reflectance) and scanning electron microscopy (SEM), respectively. Results were discussed by comparing the stabilizing efficiency of mixtures with and without phenol system. Among phenol containing systems, where we mostly observe discoloration due to the oxidation of hindered phenol and the combination of secondary HAS, tertiary HAS, organo-phosphite and hindered phenol exhibited improved stabilization efficiency than single or binary additive systems. The mixture of secondary HAS and tertiary HAS, has shown antagonistic effect of stabilization whereas their combination with organo-phosphite has exhibited synergistic effect of stabilization even at higher doses of gamma-sterilization. The effects have been explained through the interaction between the stabilizers. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Antioxidants; discoloration; ethylene-propylene copolymer; gamma-sterilization; stabilization; tensile properties

Photo-stabilization of EPDM-clay nanocomposites: effect of antioxidant on the preparation and durability - Lonkar, Sunil P.; Kumar, A. Pratheep; Singh, Raj Pal (Polymers for Advanced Technologies, 2007)
The present study is to examine the photo-stabilization effect of an antioxidant on the photo-oxidation of ethylene-propylene-diene monomer (EPDM)-clay nanocomposites. During the preparation of EPDM-clay nanocomposites via melt processing antioxidants are usually incorporated along with clay, which allows phenolic antioxidant molecules to get adsorbed onto acidic clay platelets and their interaction with metallic impurities reduces the stabilizing efficiency of the antioxidant. The nanocomposites were obtained by solution dispersion followed by melt compounding of EPDM and organophilic montmorillonite (OMMT). The samples were characterized by conventional tools such as X-ray diffraction (XRD), Fourier Transform Infra Red (FT-IR) spectroscopy, and thermo-gravimetric analysis (TGA). It was found, upon photo-irradiation (lambda > 290 nm) studies by following the changes in functional groups and surface morphology, that photo-degradation was lowered by the antioxidant and the efficiency of the antioxidant could be improved by initial incorporation of antioxidant in the EPDM matrix. In EPDM-clay nanocomposites, a stabilizing activity of the antioxidant was observed above some threshold concentration of the antioxidant. The relationship between the nanoclay reinforcement and stabilizing efficiency in terms of photo-oxidation and surface morphology for their applicability are discussed. The methodology adopted for this study is also justified through our observation. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: ethylene-propylene-diene monomer; nanocomposites photo-degradation antioxidant and stabilization

Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers. part II. polypropylene matrix - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2007)
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Effect of gamma-dose rate on crystallinity and morphological changes of gamma-sterilized biomedical polypropylene - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2009)
The present work is aimed to study the changes in crystallinity and morphology of biomedical polyolefins after gamma-sterilization. The isotactic polypropylene (iPP) films were sterilized by gamma-radiation and the changes were characterized by differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and atomic force microscopy (AFM) techniques. The effect of dose rate on crystallinity changes also was focused. It was found that crystallinity and morphology significantly changed with gamma-irradiation. There was an increase in crystallinity Lip to 10 kGy accompanied with decrease in viscosity and mechanical properties. The changes in crystallinity mainly depend on gamma-irradiation dose and dose rate. The rise in crystallinity was attributed to chain scission and forming new perfect lamellae. However, the reduction was accompanied by occurrence of gamma- and beta-phases and crosslinking. Possible explanations for transitions in phases are also discussed based on our results. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Crystallinity; Dose rate; Gamma radiation; mechanical properties; Morphology; polypropylene

Single step synthesis and properties of M/MFe2O4 and PVDF/M/MFe2O4 (M = Co, Ni) magnetic nanocomposites - Deka, Sasanka; Joy, Pattayil Alias; Kumar, A. Pratheep (Science of Advanced Materials, 2009)
Metal/ferrite nanocomposites (M/MFe2O4; M = Co, Ni), consisting of nanoparticles of a metal and the corresponding metal ferrite, have been synthesized under in situ conditions by a simple and single step process. The metal/ferrite nanocomposites embedded in a polymer matrix have been prepared by a simple hot-pressing method. The performance parameters such as magnetization, coercivity, permeability and dielectric constant of the two- and three-phase nanocomposite systems are compared. The coercivity increases and the permeability decreases with increasing polymer content in the three-phase composite. Enhancement of the dielectric constant is observed at low frequencies.
Keywords: Dielectric; Ferrite; magnetic properties; Nanocomposite; Nanocrystalline; permeability